2010
DOI: 10.1507/endocrj.k09e-212
|View full text |Cite
|
Sign up to set email alerts
|

Small-cell Carcinoma of the Endometrium Presenting as Cushing's Syndrome

Abstract: Abstract. Small-cell carcinoma (SCC) of neuroendocrine type is an uncommon tumor of the endometrium. no previous report has documented Cushing's syndrome due to ectopic aCTH production by SCC of the endometrium. We describe a 56-year-old Japanese woman with SCC of the endometrium and multiple lung metastases presenting as Cushing's syndrome. The patient was referred to our hospital because of general fatigue with facial and leg edema, and multiple nodular lesions in the bilateral lungs on chest X-ray examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 17 publications
(15 reference statements)
0
32
0
Order By: Relevance
“…On the other hand, the present case occurred in association with endometrial NSCC, which is a rare disease (less than 1 % of all endometrial cancers) [13]. Some cases of endometrial NSCC have been reported to exhibit paraneoplastic syndrome in relation to neurological or endocrinological symptoms because of its neuroendocrinological nature [14][15][16][17]. In terms of renal involvement, one case each of membranous nephropathy [18] and mesangial proliferative glomerulonephritis [19] have been reported, both of which were considered to be immunocomplex deposition disease in relation to tumor-associated antigens.…”
Section: Discussionmentioning
confidence: 86%
“…On the other hand, the present case occurred in association with endometrial NSCC, which is a rare disease (less than 1 % of all endometrial cancers) [13]. Some cases of endometrial NSCC have been reported to exhibit paraneoplastic syndrome in relation to neurological or endocrinological symptoms because of its neuroendocrinological nature [14][15][16][17]. In terms of renal involvement, one case each of membranous nephropathy [18] and mesangial proliferative glomerulonephritis [19] have been reported, both of which were considered to be immunocomplex deposition disease in relation to tumor-associated antigens.…”
Section: Discussionmentioning
confidence: 86%
“…[66][67][68][69][70] On pathology, these tumors are characterized by sheets of small densely packed cells, hyperchromatic nuclei, high nuclear-to-cytoplasmic ratio, and positive markers for neuroendocrine differentiation on immunohistochemistry. 66,67,[69][70][71][72] Uterine small cell carcinomas exhibit aggressive behavior, local invasion, extrauterine spread, early lymph node involvement, and distant metastasis at diagnosis. 66,67,[71][72][73] Clinically, the most common symptoms include abnormal vaginal bleeding and pelvic pain.…”
Section: Gestational Trophoblastic Diseasementioning
confidence: 99%
“…66,67,[69][70][71][72] Uterine small cell carcinomas exhibit aggressive behavior, local invasion, extrauterine spread, early lymph node involvement, and distant metastasis at diagnosis. 66,67,[71][72][73] Clinically, the most common symptoms include abnormal vaginal bleeding and pelvic pain. 67,69,73 Uterine small cell carcinomas may produce and secrete metabolically active amines and peptides and cause paraneoplastic syndromes, including syndrome of inappropriate secretion of antidiuretic hormone, retinopathy, Cushing syndrome, and membranous glomerulonephritis.…”
Section: Gestational Trophoblastic Diseasementioning
confidence: 99%
See 2 more Smart Citations